ESTETIK DALAM PERANCANGAN PRODUK: ANTARA YANG KONKRIT DAN YANG ABSTRAK - Embun Kenyowati (Universitas Trisakti, 2007)
AbstractAesthetic has been a word with many meanings. The common one means beauty. Actually, a branch of philosophy in the field of axiology, a realm of values. As a discipline it is usually confused with the philosophy of art. The idea that aesthetic always concern with beatify and art, makes the term exhausted. in this paper, in relation with the product design, I proposed to use the original meaning of aesthetic, in Greek, aesthetic, means sensation, perception or feeling. Starting from the clear ground of the term, we can move into the idea of aesthetic of product design. In this case we are now free to use any kind of aesthetic criteria in designing or making a product, as long it accommodates people need and images, such as identity, ideology, culture, class etc. No one can dictate or judge any other person 's aesthetic, in the name of high culture, or whatever, so this is to be a knowledge by the product designer, or first by the design institution, and the students at large. Though the value of classical products can be still high in your wind and in reality, but now it is at the same level with the ethilic, for example both are aesthetic. It is a matter of understanding and reconciling between the concrete and the abstract. Between the thing, the product, and the ideas or values you would like to attribute to it.Keywords: aesthetic, art, sensation, experienceAbstrakEstetika acialah kata dengan banyak arti. Umumnya adalah keindahan. Sebagai suatu disiplin ilmu, estetika sering tertukar dengan filsafat seni. Pendapat bahwa estetika selalu menyangkut keindahan dan seni membuat istilah estetika menjadi samar. Dalam Hubungannya dengan desain produk saya mengajukan untuk menggunakan pengertian estetika sebenarnya, yang dalam bahasa Yunani berarti sensasi, persepsi atayu perasaan. Dimulai dari kaidah yang berlaku, dalam bahasa ini , kaitan estetika dengan desain produk. Dalam kasus ini kita bebas menggunakan kriteria estetika dalam mendesain atau membuat produk, selama hal itu tetap memberi gambaran identitas, ideologi , kebudayaan, golongan dan sebagainya. Tidak ada orang yang bisa menilai estetika orang lain, biarpun atas nama kebudayaan tinggi, jadi ini merupakan ilmu bagi deainer produk/institusi desain, dan mayoritas siswa